EFEKTIVITAS DOSIS FERRI KLORIDA (FeCl3) DALAM MENURUNKAN KADAR CHEMICAL OXYGEN DEMAND (COD) PADA LIMBAH PABRIK TAHU DI TEMPELSARI KALIKAJAR WONOSOBO - Nelly Rofiatul Umah; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Tofu liquid waste to contain high COD that cause environmental pollution and adverse health effects. Based on preliminary studies, COD level of liquid waste in tofu was 5.600 mg/l and 5.120 mg/l. This level exceeds standart quality of COD in tofu liquid waste is 275 mg/l. Therefore, it is necessary to treat wastewater, with coagulation-focuculation system using ferri chloride coagulant. The purpose of this study was to determined the effectiviness of ferric chloride to reduced COD level in tofu liquid waste. The type of research was true experimental research with pretest-postest wiith control group design. The sample in this research was tofu liquid waste in Tempelsari, Kalikajar, Wonosobo taken directly from the factory. Total sample for 6 treatment (7 gr, 9 gr, 11 gr, 13 gr, 15 gr and 17 gr) with 4 replication was 32 samples. Data analysis used Kruskal Wallis test showed that there was difference average in decreasing COD level of tofu liquid waste with various dose of ferri chloride (p-value = 0,0001). The result of Man Whitney test, showed that all treatments given to the waste ample had significant differences in lowering the COD level of tofu waste (p ≤ 0,05). The average COD after treatment has decreased gradually as more doses of ferri chloride. The large of efficiency was in the dose 17 gr with a decrease percentage was 90,74% or can decreased COD to 463,25 mg/l. The ability of ferri chloride in reducing COD of liquid waste in tofu has not been able to score up to below Central Java Regulation no. 5 Year 2012 of 275 mg/l. Therefore, the need for further treatment with biological treatment such as using water hyacinth.